2020
DOI: 10.1002/admi.201901820
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Electromagnetic Wave Absorption of Supramolecular Isomer‐Derived Nanocomposites with Different Morphology

Abstract: Design and fabrication of highly efficient electromagnetic wave absorbing materials are yet challenging tasks, mainly caused by the lack of the in‐depth understanding of structure–property relationship. Herein, significant morphology effect on electromagnetic wave absorption is uncovered by pyrolyzing two isomeric metal–organic frameworks (MOFs: MIL‐101‐Fe and MIL‐88B‐Fe). The resultant pyrolyzed nanocomposites from these two MOFs with different topology under same pyrolysis condition have almost identical che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(33 citation statements)
references
References 70 publications
(25 reference statements)
0
33
0
Order By: Relevance
“…The RL value reached − 52.9 dB at 3.07 mm, corresponding to an EAB of 4.64 GHz. Miao et al reported two isomeric MOFs (MIL-101-Fe with octahedral shape and MIL-88B-Fe with rod shape) derived Fe/C by pyrolysis at Ar atmosphere and studied the effect of morphology on EMW absorption [ 127 ]. Attributed to more abundant graphite flakes in MIL-101-Fe-derived Fe/C, the minimum RL value could reach − 59.2 dB with a thickness of 4.32 mm, and the EAB could achieve 5 GHz with a thickness of 1.8 mm.…”
Section: Carbon-based Mof Derivatives For Emw Absorption Applicationsmentioning
confidence: 99%
“…The RL value reached − 52.9 dB at 3.07 mm, corresponding to an EAB of 4.64 GHz. Miao et al reported two isomeric MOFs (MIL-101-Fe with octahedral shape and MIL-88B-Fe with rod shape) derived Fe/C by pyrolysis at Ar atmosphere and studied the effect of morphology on EMW absorption [ 127 ]. Attributed to more abundant graphite flakes in MIL-101-Fe-derived Fe/C, the minimum RL value could reach − 59.2 dB with a thickness of 4.32 mm, and the EAB could achieve 5 GHz with a thickness of 1.8 mm.…”
Section: Carbon-based Mof Derivatives For Emw Absorption Applicationsmentioning
confidence: 99%
“…The morphology usually had significant effect on the MA performance. Kong pyrolyzed two MOFs with different topologies (MOFs: MIL-101-Fe and MIL-88B-Fe) under same pyrolysis condition, identical chemical composition and microstructure [ 155 ]. The RL max is − 59.2 dB with a thickness of 4.32 mm, and the EAB is 6.5 GHz with a thickness of 2 mm which are achieved by Fe/C-700@101 (700: pyrolysis temperature; 101: MIL-101 precursor) and Fe/Fe 3 C/C-800@101, respectively.…”
Section: Mof-derived Pc-based Nanocomposites As Mamsmentioning
confidence: 99%
“…[7][8][9][10] To be a high performing EM absorbing material, the absorption intensity, termed as reection loss value (RL), needs to be as low as possible. 11,12 In general, an RL value of À10 dB has been the qualied value, corresponding to 90% of the absorption coefficient. [13][14][15] The frequency band with RL < À10 dB is a crucial factor to estimate the EM absorption performance.…”
Section: Introductionmentioning
confidence: 99%